Analysis of Polish healthcare system fianancing in 2000-2009 - Joanna Hady; Małgorzata Leśniowska (e-Finanse: Financial Internet Quarterly, 2013)
Healthcare is a very important, and at the same time difficult element of each state's policy. For many countries, the issue of financing the healthcare system is a delicate matter, while at the same time one of the basic economic and social issues. Nevertheless, decisions concerning the sources and principles of healthcare financing influence the quality of the entire system. This article analyses the expenditure on healthcare in Poland during the last few years. It presents total expenditure on healthcare, its yearly growth rate, as well as other data related to the expenses incurred within the Polish healthcare system in that period.
Keywords: I11; I15; I18; 330; Poland; health care; financing system